Theory and applications of satisfiability testing - SAT 2013 : 16th International Conference, Helsinki, Finland, July 8-12, 2013. Proceedings - Van Gelder, Allen; Järvisalo, Matti (Lecture Notes in Computer Science,, 2013)
This book constitutes the refereed proceedings of the 16th International Conference on Theory and Applications of Satisfiability Testing, SAT 2013, held in Helsinki, Finland in July 2013. The 21 regular papers, 5 short papers, and 5 tool papers presented together with 3 invited talks were carefully reviewed and selected from 71 submissions ( 50 regular, 15 short  and 6 tool papers). The focus of the papers in on following topics: maximum satifiability, encodings and applications, solver techniques and algorithms, clique-width and SAT, propositional proof complexity, parameterized complexity.